Diacetyl and Other Ketones in e-Cigarette Aerosols: Some Important Sources and Contributing Factors - McAdam, Kevin; Waters, Gareth; Moldoveanu, Serban; Margham, Jennifer; Cunningham, Anthony; Vas, Carl; Porter, Andrew; Digard, Helena (Frontiers in Chemistry, 2021)
Background: Concerns over the presence of the diketones 2,4 butanedione (DA) and 2,3 pentanedione (AP) in e-cigarettes arise from their potential to cause respiratory diseases. Their presence in e-liquids is a primary source, but they may potentially be generated by glycerol (VG) and propylene glycol (PG) when heated to produce aerosols. Factors leading to the presence of AP, DA and acetoin (AC) in e-cigarette aerosols were investigated. We quantified direct transfer from e-liquids, examined thermal degradation of major e-liquid constituents VG, PG and 1,3 propanediol (1,3 PD) and the potential for AC, AP and DA production from sugars and flavor additives when heated in e-cigarettes. Method: Transfers of AC, AP and DA from e-liquids to e-cigarette aerosols were quantified by comparing aerosol concentrations to e-liquid concentrations. Thermal generation from VG, PG or 1,3 PD e-liquids was investigated by measuring AC, AP and DA emissions as a function of temperature in an e-cigarette. Thermal generation of AC, AP and DA from sugars was examined by aerosolising e-liquids containing sucrose, fructose or glucose in an e-cigarette. Pyrolytic formation of AP and DA from a range of common flavors was assessed using flash pyrolysis techniques. Results: AC transfer efficiency was >90%, while AP and DA were transferred less efficiently (65%) indicating losses during aerosolization. Quantifiable levels of DA were generated from VG and PG and to a lesser extent 1,3 PD at coil temperatures >300°C. Above 350°C AP was generated from VG and 1,3 PD but not PG. AC was not generated from major constituents, although low levels were generated by thermal reduction of DA. Aerosols from e-liquids containing sucrose contained quantifiable (>6 ng/puff) levels of DA at all sucrose concentrations tested, with DA emissions increasing with increasing device power and concentration. 1% glucose, fructose or sucrose e-liquids gave comparable DA emissions. Furanose ring compounds also generate DA and AP when heated to 250oC. Conclusions: In addition to less than a quantitative direct transfer from the e-liquid, DA and AP can be present in the e-cigarette aerosol due to thermal decomposition reactions of glycols, sugars and furanonse ring flavors under e-cigarette operating conditions.